Experimental investigation of a point-absorber wave energy converter response in different wave-type representations of extreme sea states. (15th March 2022) - Shahroozi, Zahra; Göteman, Malin; Engström, Jens
Abstract: The experimental results of a 1:30 scaled wave tank experiment of a point-absorber in extreme sea states and intermediate water depth are studied. The effect of the PTO damping parameter and different non-linear phenomena in extreme wave conditions such as wave breaking and overtopping are investigated with the focus on the maximum line (mooring) force in the presence of an upper end-stop. In the comparison of different wave-type representations, i.e. irregular, regular, and focused waves, of the same sea state, not all the wave types necessarily yield to the same peak line force. Moreover, there exists an optimum damping value for each sea state in which the smallest peak force is achieved. Both end-stop spring compression and wave breaking slamming result in peak line forces which may be compensated by overtopping water pressure. Large surge motion is obtained for waves with a long wavelength which can contribute to higher and more damaging line forces. Highlights: Wave tank experiment of a 1:30 scaled point-absorber wave energy converter subjected to extreme waves. Effect of power take-off damping, different wave-type representations, and end-stop spring on the peak line force. Influence of non-linear phenomena such as over-topping, wave breaking, and slamming on the line force.